The significance of the internal control system implementation on village government performance - S., Mulyani,; D.A., Munir,; B., Akbar,; M., Yoseph,; ., Sudrajat (Opción, 2020)
This study aims to examine the effectiveness of an internal control system on village governance performance based on frauds found in village fund management. Primary data were collected by surveying 270 village governments. The data analysis was performed using the Structural Equation Model (SEM). The results found that when the internal control system was weakly implemented, the fraud in village fund management would increase, which led to the declined performance of the village government. In conclusion, effective internal control can reduce fraud levels in village funds. Besides, such control will bring a positive impact on improving the village government’s performance